CAPTAIN MARVEL: KESETARAAN GENDER DALAM PERSPEKTIF TOKOH SUPERHERO - Nur Amir Fauzi (Institut Seni Indonesia Yogyakarta, 2019)
Captain Marvel: Gender Equality in the Perspective of Superhero. Gender equality is something that can be a concern lately so it can be used as an issue in the creation of a work of art, because the ‘value’ of women is considered lower than men in various activities or daily activities. A big American movie studio, Marvel Studios, released a film with a female superhero named Captain Marvel. The emergence of the film made the writer want to examine about this superhero much deeper. The method employed for this paper was deconstruction approach by linking it to the phenomenon occurring in the society. Hopefully this article will strengthen the perspective of gender equality by studying the character of Captain Marvel through her portrayed character, sign, and color of her superhero costume. Keywords: Captain Marvel, gender equality, superhero, Marvel Studios, movie